Dopamine incorporating forward osmosis membranes with enhanced selectivity and antifouling properties. Issue 40 (20th June 2018) - Wang, Yi; Fang, Zhendong; Zhao, Shuaifei; Ng, Derrick; Zhang, Juan; Xie, Zongli
Abstract : Incorporation of dopamine enhanced selectivity and antifouling properties of novel TFC polyamide FO membranes. Abstract : A new type of polyamide thin-film composite forward osmosis (FO) membranes were prepared by controlling dopamine self-polymerization in the aqueous phase during interfacial polymerization. The as-prepared membranes were investigated by attenuated total reflection Fourier transform infrared, X-ray photoelectron spectroscopy, field-emission scanning electron microscopy, atomic force microscopy and water contact angle measurements. The influence of the dopamine self-polymerization degree with different polydopamine particle sizes on membrane morphologies and chemical properties was studied by regulating dopamine concentrations in the aqueous phase. FO performance of the membrane was evaluated under two different modes, i.e. active layer facing draw solution (AL-DS) and active layer facing feed solution (AL-FS). The optimized FO membranes achieved a doubly enhanced water flux (22.08 L m −2 h −1 ) compared with the control membrane without dopamine incorporation, and a half-reduced reverse salt flux (32.77 mmol m −2 h −1 ) with deionized water as the feed and 1 M NaCl as the draw in the AL-FS mode. The optimized FO membrane showed a significantly reduced structural parameter (176 μm) compared with the control membrane (635 μm), indicating the minimised internal concentration polarization. Moreover, the new FO membranes had less flux decline than the control membrane, suggesting the improved antifouling performance of the membrane. Incorporation of dopamine during interfacial polymerization can be an effective strategy to fabricate high-performance FO membranes with excellent antifouling properties.